Kode Vicious Coder's Block. - Neville-Neil, George V. (Communications of the ACM, 2011)
The author opines regarding the subject of coder's block, the occasional inability of computer programmers to work productively in creating computer code. Office distractions are cited as a primary factor in coder's block and tips for managing time to enhance productivity are discussed. Office email, instant messaging, and social networking are isolated as significant distractions to programming productivity.